2004
DOI: 10.1523/jneurosci.3442-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Brain Region-Specific Forms of Obesity by Agouti

Abstract: Disruption of melanocortin (MC) signaling, such as by ectopic Agouti overexpression, leads to an obesity syndrome with hyperphagia, obesity, and accelerated body weight gain during high-fat diet. To investigate where in the brain disruption of MC signaling results in obesity, long-term Agouti expression was induced after local injections of recombinant adeno-associated viral particles in selected brain nuclei of adult rats. Agouti expression in the paraventricular nucleus, a hypothalamic region with a high den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…A feature of AAV2 transduction in the brain is that the vector remains confined to the injection site (Passini et al, 2004;Sin et al, 2005). Indeed, our previous findings, using a similar strategy to overexpress peptide, showed that immunostaining was limited to the injected area, and not observed in projection areas (Kas et al, 2004;Tiesjema et al, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…A feature of AAV2 transduction in the brain is that the vector remains confined to the injection site (Passini et al, 2004;Sin et al, 2005). Indeed, our previous findings, using a similar strategy to overexpress peptide, showed that immunostaining was limited to the injected area, and not observed in projection areas (Kas et al, 2004;Tiesjema et al, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…1,2 Constitutive inhibition of the MC-Rs through ectopic overexpression of AgRP or agouti, or central infusion of AgRP, results in hyperphagia and reduces energy expenditure. [3][4][5][6][7][8] Furthermore, knockout studies have shown that reduced activity of the MC3R and MC4R contribute to obesity and these receptors have additive effects when both are deleted. [9][10][11][12][13][14] Although reduced activation of brain MC-Rs results in obesity, it is poorly understood where in the brain this effect is mediated as the MC-Rs are expressed in multiple sites of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] We previously showed that ectopic overexpression of Agouti in the paraventricular nucleus (PVN) of rats resulted in hyperphagia and obesity. 8 In addition, local acute injection studies with AgRP 83À132 and MC-R antagonists in different brain nuclei demonstrated that when MC-R activity is reduced, food intake is stimulated. [18][19][20] Thus, multiple brain regions are involved in the effects of MC-Rs on food intake.…”
Section: Introductionmentioning
confidence: 99%
“…MC4R is broadly expressed in many brain areas implicated in the regulation of energy balance (Mountjoy et al 1994, Kim et al 2000, Lu et al 2003, Kas et al 2004. One of the brain regions that highly express MC4R is the paraventricular nucleus of the hypothalamus (PVN) (Mountjoy et al 1994, Lu et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Microinjection of MC4R agonists MTII or a-MSH into the PVN inhibits food intake, whereas microinjection of MC4R antagonists AgRP, SHU9119 or HS014, into this region stimulates food intake (Cowley et al 1999, Kask et al 2000, Kim et al 2000, Wirth & Giraudo 2001. It has also been demonstrated that overexpression of MC4R antagonist agouti in the PVN using adeno-associated virus (AAV) causes increased food intake and body weight (Kas et al 2004). These pharmacological data support the importance of MC4R activity in the PVN in the control of appetite and body weight.…”
Section: Introductionmentioning
confidence: 99%